Relationship Between Perception of Electric Cigarette and Electric Smoking Behaviour - Purwanti, Ika Setya; Devhy, Ni Luh Putu; Faidah, Nurul (Basic and Applied Nursing Research Journal, 2023)
Introduction: The adolescent has a high chance of becoming a smoker. Numerous determinants impact the smoking conduct of adolescents, among which the companionship of peers holds significant sway. The study aims to investigate the level of awareness pertaining to e-cigarettes as a means of acquiring insights into the patterns of e-smoking conduct. Methods: The study used a cross-sectional design in Kemoning Traditional Village, with 87 adolescents and early adults. Results: there is a strong link between adolescent smokers' perceptions of the calmness that comes with smoking and their actual smoking behaviour (p = 0.043). Conclusion: Participants generally had a positive perception of smoking hazards, with most agreeing that smoking could have negative health effects. Overall, the study provides insights into the factors influencing smoking behaviour.